Currency substitution: evidence from latin america - Prock, Jerry; Soydemir, Gokce; Abugri, Benjamin A (Journal of Policy Modeling, 2003)
Currency substitution represents a shift from domestic currency to foreign currency and is often related to times of high and variable inflation. In this paper, we investigate the extent of currency substitution in Argentina, Brazil and Mexico using a vector error correction (VEC) model. We empirically test this hypothesis by introducing artificial shocks to the system of equations and find that M1 response to a one standard deviation increase in that country's interest rate is negative and significant for Argentina and Brazil but not for Mexico. An artificially introduced one standard deviation increase in nominal exchange rate results in a statistically significant increase in M1 in Argentina and Brazil but again not for Mexico. Based on the patterns of the impulse response functions (IRFs) and the magnitude of the coefficients, we conclude that currency substitution occurs to a greater extent in Argentina and Brazil than Mexico. This is reflective of the implementation of relatively more credible macroeconomic policies in Mexico after the December 1994 crisis. Thus from a policymaking perspective, it is important to consider that the greater the degree of currency substitution, the more sensitive a country's monetary aggregates are to sudden movements in exchange rates, productivity and interest rates. (C) 2003 Society for Policy Modeling. Published by Elsevier Science Inc. All rights reserved.
Keywords: Currency; Latin America; Substitution; VEC; dept.eco; dept.fin

Book Review: Birthquake: the baby boom and its aftershocks. by diane j. macunovich. chicago: the university of chicago press, 2002. pp xiii, 314. 37.50 - Mills, Judith Woerner (The Journal of Economic History, 2003)
Keywords: book.review; dept.eco; dept.fin